Combining active learning and graph-based semi-supervised learning - Candao, Jhonatan; Berton, Lilian (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC), 2019)
The scarcity of labeled data is a common problem in many applications. Semi-supervised learning (SSL) aims to minimize the need for human annotation combining a small set of label data with a huge amount of unlabeled data. Similarly to SSL, Active Learning (AL) reduces the annotation efforts selecting the most informative points for annotation. Few works explore AL and graph-based SSL, in this work, we combine both strategies and explore different techniques: two graph-based SSL and two query strategy of AL in a pool-based scenario. Experimental results in artificial and real datasets indicate that our approach requires significantly less labeled instances to reach the same performance of random label selection.